Rapid improvement of angiostenosis due to isolated middle cerebral artery dissection: A case report. Issue 4 (January 2018) - Zhang, Li; Nan, Guangxian; Mao, Ying; Chi, Lumei
Abstract: Rationale: Intracranial arterial dissection is a rare cause of ischemic stroke, and isolated middle cerebral artery dissection (MCAD) is extremely rare, having been described only in sparse case reports. The etiology, clinicoradiological features, and treatment strategies are not yet well understood. Patient concerns: A 49-year-old man presented with rapidly progressive aphasia and motor disturbance of the right limbs. Diagnoses: Neuroimaging evaluation confirmed a diagnosis of MCAD and cerebral infarction. Interventions: The patient underwent oral anti-platelet therapy (100 mg aspirin daily). Outcomes: The patient recovered to normal status within 2 weeks following antiplatelet treatment. During a follow-up period of 2 years, he remained neurologically asymptomatic and led a virtually normal life. Lessons: It is crucial for clinicians to be aware of this entity, as the diagnosis of MCAD is quite challenging. Antiplatelet therapy is effective for treating this condition, and the prognosis can be favorable.